Advanced empirical formulae for the ultimate strength assessment of continuous hull plate under combined biaxial compression and lateral pressure. (15th June 2023) - Li, Dongyang; Chen, Zhen
Highlights: Ultimate strength of continuous hull plate under combined loads is investigated considering elastic rotational constraint. An equivalent loading method is validated based on the comparison with proportional loading approach. A large number of non-linear finite element simulations are conducted to derive the empirical formulae. Applicability and accuracy of the proposed explicit formulae are acceptable. Abstract: This paper focuses on developing empirical formulae for the hull structural design and safety estimation. An equivalent sequential loading method for biaxial compression is verified and adopted to realize decoupling the conventional implicit strength relationship of plates expressed by elliptic function. In total, 2737 and 1944 scenarios regarding the combinations of slenderness ratio, aspect ratio and applied loads are selected to perform non-linear finite element analysis for longitudinal and transverse ultimate strength, respectively. Influences of considered parameters on the ultimate limit state behaviours are documented and clarified aiming to provide some useful insights for the load-carrying capacity assessment. Based on the outcomes of numerical investigation, two empirical formulae with the same general explicit shape, which can be utilized in various load scenarios including not only combined biaxial compression and lateral pressure but also other load combinations, are proposed through response surface method. According to the statistical analysis, the equations show good agreement with the ABAQUS simulation results ( R  = 0.993 and 0.996), confirming they can be used as a practical design technology in the ultimate strength assessment.